2018
DOI: 10.1002/jbm.b.34198
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of anti‐fibrotic effects of select cytokines for vocal fold scar treatment

Abstract: Scarring of the vocal fold lamina propria (LP) can cause considerable voice disorders due to reduced pliability in scar tissue, attributed in part to abnormal extracellular matrix (ECM) deposition produced by the fibrotic vocal fold fibroblast (fVFF). Cytokines with anti-fibrotic potential have been investigated to limit abnormal LP ECM, but are limited by the need for repeat injections. Moreover, the potentially significant role played by activated macrophages (AMOs) is usually not considered even though the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 103 publications
(157 reference statements)
1
15
0
Order By: Relevance
“…47 Exogenous HGF administration was thought to have a significant endogenous antifibrotic effect on VF scarring, which has been associated with the improvement of lamina propria biomechanical properties, including reversing undesirable ECM production and promoting endogenous HGF expression in vivo 48,49 (Table II) and in vitro. 50,51 These data support the therapeutic potential of HGF for lamina propria scar treatment. The purpose of preclinical studies is to determine reasonable concentrations, reveal pharmacokinetics, and evaluate the safety of HGF administration.…”
Section: Hgf Therapysupporting
confidence: 53%
See 1 more Smart Citation
“…47 Exogenous HGF administration was thought to have a significant endogenous antifibrotic effect on VF scarring, which has been associated with the improvement of lamina propria biomechanical properties, including reversing undesirable ECM production and promoting endogenous HGF expression in vivo 48,49 (Table II) and in vitro. 50,51 These data support the therapeutic potential of HGF for lamina propria scar treatment. The purpose of preclinical studies is to determine reasonable concentrations, reveal pharmacokinetics, and evaluate the safety of HGF administration.…”
Section: Hgf Therapysupporting
confidence: 53%
“…This period is regarded as the key period for the remodeling of VF scars 47 . Exogenous HGF administration was thought to have a significant endogenous antifibrotic effect on VF scarring, which has been associated with the improvement of lamina propria biomechanical properties, including reversing undesirable ECM production and promoting endogenous HGF expression in vivo 48,49 (Table 2) and in vitro 50,51 . These data support the therapeutic potential of HGF for lamina propria scar treatment.…”
Section: Resultsmentioning
confidence: 73%
“…Recently, Chen et al demonstrated that a decrease in pro-inflammatory markers (TNF-α, IL-6) and an increase in anti-inflammatory markers (i.e., IL-10/IL-12) may favor antifibrotic outcomes via reduction in fibrotic proteins and supported the therapeutic potential of HGF and IL-10 for VF scar treatment using in vitro models [109]. These perspectives would bring the light of hope on future strategies targeting specific activated macrophages phenotypes for establishing an anti-inflammatory approach for the VF scar.…”
Section: New Strategies For Vf Scar Including Regenerative Medicinmentioning
confidence: 99%
“…The antifibrotic effects of several cytokines were evaluated in an in vitro study by Chen et al [ 39 ] as vocal fold scar treatment. Their results showed that IL-6 and IL-10 displayed an antifibrotic and anti-inflammatory action in vitro, providing a possible new solution in cases of vocal fold scarring.…”
Section: Introductionmentioning
confidence: 99%